Hemorrhagic Brain Metastases: A Diagnostic Dilemma and Diagnosis of Exclusion - Meel, Mukta; Bhaskar, Mukesh Kumar; Jindal, Arpita (Indian Journal of Neurosurgery, 2022)
Pleomorphic carcinoma is a malignant and aggressive primary lung carcinoma that occurs at a rate of approximately 0.3%. This rarely encountered tumor may present a diagnostic challenge to neuroradiologists and pathologists, as it has propensity to present as hemorrhagic brain metastasis with unknown primary and result in delay in diagnosis that could impact clinical outcome. Herein, we report a unique case in its presentation in a 56-year-old female, having symptomatic brain metastasis prior to the discovery of the pulmonary lesion.
Keywords: hemorrhagic brain metastasis; lung carcinoma; pleomorphic carcinoma